EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN PBI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMA NEGERI 1 BARUMUN SELATAN - Nanda Sri Sukma Dewi Nasution (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to describe the effectiveness of using PBI (Problem Based Instruction) learning model on students’ mathematical communication ability at the eleventh grade students of SMA Negeri 1 Barumun Selatan. The research was conducted by applying experimental method (one group pretest posttest design) with 26 students as the sample and they were taken by using cluster sampling technique from 108 students. Observation and test were used in collecting the data. Based on the data analysis, it was found that: (1) the average of using PBI learning model was 3.36 (very good category) and (2) the average of students’ mathematical communication ability before using PBI learning model was 56.75 (fair category) and after using PBI learning model was 92.19 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant influence of using PBI (Problem Based Instruction) learning model on students’ mathematical communication ability at the eleventh grade students of SMA Negeri 1 Barumun Selatan. Key words: PBI learning model , mathematical communication ability